Implementasi Akad Salam Dalam Transaksi Jual Beli Di Toko Salamah - Sri Sudarti; Fahmi Azhar Nasution (CERED Indonesia Institute, 2022)
This study aims to determine the extent of consumer knowledge of the implementation of the salam contract at the Salamah store and to determine the mechanism of the salam contract in the sale and purchase transaction at the Salamah store. This research method uses qualitative research. Data collection techniques used in this study were observation, interviews, and documentation. while the data analysis in this study used data reduction. The data validity technique uses the triangulation method. Based on the results of research and data analysis, it can be concluded that many consumers in Salamah Stores do not know the term salam contract, but consumers understand the salam contract system because consumers are familiar with the term pre-order which has a similar system. The implementation of the salam contract at the Salamah shop is correct and in accordance with sharia. The mechanism of the salam contract at the Salamah Shop is that the buyer orders goods from the seller. Next the seller makes sure the goods are available at wholesalers. The buyer then makes payment in full. The seller orders the goods to the wholesaler and makes the payment. Then the goods are sent from the wholesaler to the seller.